SYNTHETIC STUDIES ON STEROIDAL ALKALOIDS (1966)
In the first part of this thesis, a brief survey of the chemistry of veratramine viz. its occurrence, isolation and structural diagnosis is given. This part also includes a review of recent work on the stereochemistry and the synthetic work of other workers on the alkaloid. The main section describes three approaches to the synthesis of the C-Nor-D-homo ring system of the veratrum alkaloids. Howell and Taylor’s acetate diester 6(β-acetoxy-1 β:2αdi (methoxy carbonyl methyl)-9β-methyl-trans decalin prepared from 2:3:4:9:10:12- hexahydro-6-methoxy-12-methyl-2-oxophenanthrene was successfully cyclised to the potential intermediate 6(β -acetoxy-1 β:2α-( cyclopen- tan-3-one)-9-methyl-trans decalin. The pentanone was ring extended to give a solid substance which certainly contained the steroidal ring system of veratramine but which could not be obtained in the pure form. Attempts aimed at an easier preparation of the pentanone acetate by alkylating 1-oxo-6-ethoxy-8a-methyl-1,2,3,7,8, 8a hexahydro naphthalene with different alkylating agents were unsuccessful, the starting material being recovered in each case. In a second approach, 1-(2-cyanoethyl)-2-hydroxy naphthalene was converted to 2:3:4:9:10:12-hexahydro-6-methoxy-7-(3-bromo- propyl)-12-methyl-2-oxophenanthrene and 8-oxo-10a-methyl-1,2,3,4,5,6,8,9,10,10a-decahydro-1-oxa chrysene. The benzene nucleus of either intermediate was resistant to reduction and so they could not be used for further work. In the last attempt, 2-benzoyloxy-1,2,3,4,5,6,7,9,10,11,12,13 dodecahydro-12-methyl-7-oxophenanthrene was prepared starting with 2-naphthol and the tricyclic enone was successfully condensed with 2,2-ethylenedioxy-5-bromo pentan-2-one in the presence of potassium t-butoxide in t-butanol. The adduct was successively reduced, reacted with methyl magnesium bromide, deketalized y acetylated, ozonised and cyclised to give an oily substance which contained the veratramine steroidal nucleus as revealed by its U.V. spectrum. The oil did not crystallize. An oil which should probably crystallize more readily could be obtained if complete reduction of the original ansaturated adduct could be accomplished in the attempts some new compounds were prepared. These were mainly naphthalene, phenanthrene and hydrochrysene compounds. I.R U.V, or N.M.R. spectroscopic data were recorded for all the new compounds and for most of the known ones. Some structural formulae are repeated in the script, so as to aid the reader’s comprehension.